Preventing free flap complications: key factors to keep in mind - Kornmann, Jonas; Schug, Rasmus; Huber, Lena; Lammert, Anne; Jungbauer, Frederic; Affolter, Annette; Rotter, Nicole; Zaubitzer, Lena; Bugia, Luis; Beck, Grietje; Scherl, Claudia (Journal of surgical oncology, 2025)
Background and Objectives Reconstruction of head and neck defects using free flaps is successful, but complications occur. This study aims to identify factors preventing complications to support clinical decision-making. Methods Retrospective study for free flap reconstructions (2019 to 2022, tertiary referral center). Univariate and multivariate regression models assessed predictors of complication-free survival (CFS) and odds ratios (OR) measured risk correlations. Results Of 125 identified cases, most patients were male (71.8%) with a median age of 66 years (37-93 years). Common complications were wound healing disorders (10.9%), hematoma (10%), total (7.3%) or partial (1.8%) flap necrosis, cardiovascular events (5.5%), and pulmonary artery embolism (4.5%). 30-day CFS was 63%. On multivariable analysis, female gender (HR: 9.4, CI: 2.6-33.5), alcohol abuse (HR: 3.5, CI: 1.4-8.4), N2-3 (HR: 2.4, CI: 1.3-4.4), obesity (HR: 2.1, CI: 0.9-5.1), preoperative anticoagulation (HR: 2.5, CI: 1.1-5.9) were significant prognosticators. Positive factors increasing CFS included high albumin (OR 0.21, p = 0.02), intraoperative i.v. heparin bolus (OR 0.15, p = 0.08), intraoperative catecholamine treatment (OR 0.15, p = 0.009), and nonsmoking (OR 0.18, p = 0.1). Conclusion Key preventive measures against complications include optimizing nutritional status and albumin levels, administering intraoperative heparin and catecholamines, and abstaining from alcohol. Females should also be screened for undiagnosed cardiovascular risks.